The Effect of Negative Message Framing on Green Consumption: An Investigation of the Role of Shame - Amatulli, Cesare (Journal of business ethics, 2019)
Despite society’s increasing sensitivity toward green production, companies often struggle to find effective communication strategies that induce consumers to buy green products or engage in other environmentally friendly behaviors. To add clarity to this situation, we investigated the effectiveness of negative versus positive message framing in promoting green products, whereby companies highlight the detrimental versus beneficial environmental consequences of choosing less versus more green options, respectively. Across four experiments, we show that negatively framed messages are more effective than positively framed ones in prompting consumers to engage in pro-environmental behaviors. More importantly, we find that anticipated shame is the emotion responsible for this effect. Furthermore, both environmental concern and the type of product promoted serve as moderators; thus, the mediating role of anticipated shame is attenuated when environmental concern is low and the product is a luxury one. Finally, we discuss the theoretical and managerial implications of our work, along with its limitations and some directions for future research.